MALARIA IN PREGNANCY PREVENTION (MIPP) INFORMATION COMPREHENSION, MOTIVATION AND ADHERENCE AMONG ANTENATAL CLINIC ATTENDEES IN TARABA STATE SPECIALIST HOSPITAL,JALINGO, NIGERIA- A DESCRIPTIVE SURVEY. - Chiegil Solomon; Rachael Abeh Sani; Iranum Nimiruna; Simon Abafalous; Uriah Danladi; Umeh, Mercy Orji; Akilu Hamza; Grace Christopher Tanko Danjuma (Student's Journal of Health Research Africa, 2023)
Background: